Phytochemisty and Antioxidant Activity of Ethanol, Ethyl Acetate, and n-Hexane Extracts of Suruhan Leaves (Peperomia pellucida) - Arsianti, Ade; Gill, Steven; Kristanty, Diyah (UI Scholars Hub, 2025)
Background: Free radicals are natural byproducts of cellular metabolism, in which, their excessive accumulation can lead to oxidative stress, which plays a key role in the development of various chronic diseases, including cancer, cardiovascular disorders, and neurodegenerative conditions. Antioxidants are compounds capable of scavenging free radicals and minimizing oxidative damage. Peperomia pellucida, commonly known as Suruhan leaves, is a tropical herb traditionally used in folk medicine that contain bioactive compounds correlated with a strong radical-scavenging activity, suggesting its potential as a natural antioxidant source. This study aims to conduct a phytochemical analysis and evaluate the antioxidant activity of ethanol, ethyl acetate and n-hexane extracts of Suruhan leaves (P. pellucida). Method: Suruhan leaf powder obtained from Situbondo, East Java, was macerated in three different solvents of ethanol, ethyl acetate and n-hexane to produce its corresponding ethanol extract, ethyl acetate extract, and n-hexane extract of P. pellucida. The phytochemical components in P. pellucida extracts were determined using phytochemistry test. Antioxidant activity of the extracts was assessed using the DPPH method. Results: P. pellucida extracts comprise alkaloids, flavonoids, tannins, steroids, and triterpenoids as its phytochemical constituents. The ethanol and ethyl acetate extracts of P. pellucida displayed extremely strong antioxidant properties on DPPH with IC50 value of 14.45 µg/mL and 22.12 µg/mL respectively, while the n-hexane extract exhibited moderate antioxidant activity with IC50 value of 102.71 µg/mL on DPPH. Conclusion: P. pellucida extracts containing several phytochemical constituents that showed moderate-to-strong antioxidant activity towards DPPH free radical.